Growth improvement of Falcataria moluccana inoculated with MycoSilvi grown in post-mining silica sand soil medium amended with soil ameliorants - Budi Sri Wilarso; CAHYO WIBOWO; ANDI SUKENDRO; HABIB SATRIO BEKTI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Budi SW, Wibowo C, Sukendro A, Bekti HS. 2020. Growth improvement of Falcataria moluccana inoculated with MycoSilvi grown in post-mining silica sand soil medium amended with soil ameliorants. Biodiversitas 21: 422-427. High aluminum content in soil of post-mining silica sand area inhibits plant growth. MycoSilvi is an inoculum of Arbuscular Mycorrhizal Fungi (FMA) enriched with Mycorrhizal Helper Bacteria (MHBs) which plays an important role for improving plant growth in unfertile soil medium. The aims of this research were to analyze the growth response of Falcataria moluccana (Miq.) Barneby & JW Grimes) seedlings treated with MycoSilvi and soil ameliorants (compost and lime) in post-mining silica sand soil medium. The randomized complete design with factorial scheme was used in this study. The results showed that the interactions of MycoSilvi and Soil ameliorant significantly increased height, diameter, biomass and mycorrhizal colonization of F. moluccana. Combination of MycoSilvi variant 3 and lime increased height, diameter, and biomass of F. moluccana by 965%, 147%, and 1427% respectively, as compared to those of control plants. The mycorrhizal roots colonization in those treatments was 98%. The addition of compost and lime increased pH and decreased Aluminum and Fe of the soil medium. F. moluccana seedlings have high mycorrhizal dependency on post-mining silica sand soil media. These results indicate prospective uses of MycoSilvi and soil ameliorants for improving plant growth in unfertile soil medium, including soil in post-mining area.